Europe and the Digital Enlightenment: Between Autonomy and Algorithmic Power - Malik, Jozsef Zoltan (European Scientific Journal, ESJ, 2025)
This study asks whether Europe is truly living up to its Enlightenment heritage in the digital age, or whether it is drifting away from Kant’s ideal of autonomy and moving closer to Foucault’s world of invisible algorithmic control. The text compares Kant’s and Foucault’s views on the Enlightenment and explores how digital technologies-like AI and algorithms-influence personal freedom and social norms. The key question is: Are we thinking for ourselves online, or do algorithms make our choices for us? Western Europe tries to protect autonomy with laws like GDPR or DSA, but can freedom actually be guaranteed by rules from outside? Beyond this philosophical contrast, the study finds that Europe’s digital landscape reveals a growing simulation of autonomy: individuals believe they act freely, yet their actions are increasingly structured by algorithmic systems. Western Europe institutionalizes critical reason, while Eastern Europe exhibits fragmented digital autonomy shaped by distrust and weak institutions. The research concludes that Europe’s Enlightenment legacy can survive only if autonomy is redefined as technological understanding and critical reflection, rather than formal compliance.